Connecting Diversification to Performance: A Sociocognitive Approach - Ginsberg, Ari (Academy of Management Review, 1990)
This article develops a sociocognitive model of diversification that grounds the role of top managers' belief systems in the cognitive and behavioral attributes of corporate strategy. Its approach addresses several important questions: (a) How do top managers' belief systems reflect the ways in which they interpret their firms' business environments? (b) In what sense can we talk about the shared interpretations of the individuals that manage a diversified portfolio of businesses? (c) How do the characteristics of shared belief systems reflect the ability of the corporate management team to learn? (d) What specific predictions and prescriptions emerge from a sociocognitive theory of diversification?